2011
DOI: 10.1016/j.cellimm.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption decreases the percentage and number of NK cells in the peripheral lymph nodes and exacerbates B16BL6 melanoma metastasis into the draining lymph nodes

Abstract: NK cells in the lymph nodes play important roles in inhibiting tumor metastasis into draining lymph nodes. Previously, we reported that chronic alcohol consumption interferes with NK cell trafficking from the bone marrow to the spleen. Herein, we found that alcohol consumption decreases the numbers of NK cells in lymph nodes. Adoptive transfer experiments indicated that continued exposure of donor splenocytes to alcohol inhibits NK but not T cell trafficking to lymph nodes. Alcohol did not negatively affect CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…In the current study, 4 weeks of alcohol intake significantly decreased the numbers of NK cells and CD8 þ T cells and their ratios by 0.6-and 0.7-fold, respectively, in the peripheral blood (Fig. 4), which is consistent with previous studies (6,16). This result somewhat conflicts with above observation of NK cells' infiltration in liver, whereas the hepatic NK cells are also known as contributor in alcohol-induced liver injury (24).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, 4 weeks of alcohol intake significantly decreased the numbers of NK cells and CD8 þ T cells and their ratios by 0.6-and 0.7-fold, respectively, in the peripheral blood (Fig. 4), which is consistent with previous studies (6,16). This result somewhat conflicts with above observation of NK cells' infiltration in liver, whereas the hepatic NK cells are also known as contributor in alcohol-induced liver injury (24).…”
Section: Resultssupporting
confidence: 81%
“…Several epidemiologic studies presented controversial effects of alcohol consumption on cancer-associated outcomes, including survival rate and metastasis (5). An animal study showed chronic alcohol consumption accelerated melanoma metastasis into the lung by suppression of natural killer (NK) cells (6), whereas another study presented suppression of melanoma by alcohol intake via activating IFNg-producing immune cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…First, the impact of chronic EtOH feeding upon LC and DETC proliferation rates was assessed by administering BrdU to mice in the appropriate drinking liquid (i.e., EtOH solution or water), followed by the analysis of BrdU incorporation in epidermal cell suspensions. Importantly, multiple studies have used similar BrdU administration methods to assess the effects of chronic EtOH feeding upon the proliferation rates of other hematopoietic cells (Zhang and Meadows, 2005, 2009; Zhang et al, 2011). EtOH feeding differentially impacted BrdU incorporation rates of LCs and DETCs, with a significant reduction occurring in the former population but not the latter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NK cells play an important role in preventing B16 melanoma metastasis into lymph nodes [ 65 ]. We found that chronic alcohol consumption increases B16BL6 melanoma metastasis into the draining lymph nodes in mice bearing subcutaneous tumor [ 64 ].…”
Section: Effects Of Chronicmentioning
confidence: 97%
“…Due to the decrease of bone marrow-derived mature NK cells, the portion of thymus-derived NK cells, which are a population of NK cells that express IL-7Rα (CD127) and produce large amount IFN-γ upon activation, is increased in the periphery [ 36 ]. Chronic alcohol consumption inhibits NK cell migration to lymph nodes through the downregulation of CD62L expression [ 64 ]. NK cells play an important role in preventing B16 melanoma metastasis into lymph nodes [ 65 ].…”
Section: Effects Of Chronicmentioning
confidence: 99%